Implementation of B2GBPS (Broadcasting Behavior Guidelines and Broadcast Program Standards) in Disaster Journalism: Study on Cold Lava Flood News on Kompas TV May 2024 Edition - Pratiwi, Desti; Adhrianti, Lisa; Sari, Eka Vuspa (GoAcademica Research & Publishing, 2024)
Indonesia is a disaster-prone country. The high frequency of natural disasters occurring in Indonesia makes the mainstream media in this country, especially television, always flooded with coverage of these events. However, it is not uncommon for the news content to violate Article 25 of the Indonesian Broadcasting Commission's (IBC) 2012 Broadcasting Behavior Guidelines And Broadcast Program Standards (B2GBPS). This research aims to find out how Kompas TV implements Article 25 of the Broadcasting Behavior Guidelines And Broadcast Program Standards (B2GBPS) on the Cold Lava Flood Disaster in West Sumatra in the May 2024 edition. The researcher used qualitative research model and content analysis approach. As a result, Kompas TV has not fully implemented Article 25 of the Broadcasting Behavior Guidelines And Broadcast Program Standards (B2GBPS) with 13 news samples taken during the cold lava flood disaster in West Sumatra, May 2024 edition.